MrKD Gene in Environmental Isolates of Biofilm Producing Klebsiella Pneumoniae: Gen MrKD pada Isolat Lingkungan Penghasil Biofilm Klebsiella pneumoniae - Hamady, Sabah Raheem; Abas, Ismaal Jmia (Universitas Muhammadiyah Sidoarjo, 2025)
Biofilm This concept includes cell aggregates that are not attached to an interface but share traits with biofilms, such as flocs (floating biofilms) and sludge.K. pneumonia is a member of the Enterobactericeae family and is Gram-negative, non-motile, facultatively anaerobic, lactose fermentation, and is present in the environment in places like soil, vegetation, and water. It is also easily isolated from the mucosal surfaces of mammals. K. pneumoniae has at least two variants of type 3 fimbriae, with the most diversified form being the mrkD gene. Materials and Methods: Biochemical and Api20E assays were used to identify K. pneumoniae isolated from different environmental samples in Basra Governorate, Iraq, from 1/11/2021 to 1/1/2022. The Kirby-Bauer assay was performed, and biofilm phenotype formation was evaluated. Finally, the mrkD gene was detected by the PCR method. Results: results showed that the number of K.pneumoniae bacteria was 23 out of 122 samples, and then it was revealed that its ability to form biofilm was used in this study, where the two methods of Congo red were used. The presence of the mrkD gene, which is thought to be responsible for biofilm production, was investigated using a polymerase chain reaction device, and the mrkD gene was found in 34.78% of the samples. Conclusion: This research highlights that the presence of the mrkD gene in K.pneumoniae bacteria, which was isolated from different environmental samples, has a relationship with biofilm formation and shows the extent of biofilm resistance to antibiotics Highlights: Biofilm & K. pneumoniae: Forms biofilms, contains mrkD gene, resists antibiotics. Methods: Identified via biochemical tests, Kirby-Bauer assay, and PCR analysis. Results: 34.78% of isolates carried mrkD gene, linked to biofilm formation.. Keywords: Klebsiella pneumoniae, biofilms, mrkD gene.